Incidence of stroke in patients with hypertrophic cardiomyopathy in stable sinus rhythm during long-term monitoring. (3rd October 2022) - Fumagalli, C; Bonanni, F; Beltrami, M; Ruggiero, R; Zocchi, C; Tassetti, L; Maurizi, N; Zampieri, M; Lovero, F; Di Bari, M; Marchionni, N; Pieragnoli, P; et al.
Abstract: Background: Patients with hypertrophic cardiomyopathy (HCM) are at increased risk of atrial fibrillation (AF) and stroke, especially at an advanced disease stage. To date, however, the incidence and factors associated with cardioembolic events in HCM patients without AF remain unresolved. Purpose: To determine the incidence of stroke in HCM patients in whom cardiac rhythm was monitored with a cardiac implantable electronic device (CIED). The association of stroke with left atrial (LA) enlargement was also examined. Methods: Retrospective cohort study in an outpatient clinic in a tertiary HCM Referral Center. All consecutive patients diagnosed with HCM and referred for CIED implantation with >16 years at diagnosis and >1 year follow-up post CIED implantation were reviewed. Severe LA dilatation was defined as a LA dimension (LAD) of >48mm at echocardiogram. Based on CIED monitoring, patients were classified as: Pre-existing AF (diagnosed with AF prior to CIED); De novo AF (diagnosed with AF after CIED implantation); Sinus Rhythm (SR): no episodes of AF. Incidence of stroke after CIED implantation was the primary outcome. Results: A total of 185 patients (57% men, age: 54±17 years) were implanted with a CIED and were included. Pre-existing AF was present in 72 (36%) patients and de novo AF in 24 (13%); whereas 89 (48%) remained in SR. After 5 [2–9] years, stroke was reported in 19 (10.3%) patients: 7 occurred in patients with pre-existing AF (1.1%/year), 3 in patients with de novo AF (2.2%/year), and 9 in patients with SR (2.3%/year). No difference was captured by CHA2 DS2 -VASc score among rhythm categories. Patients with AF had larger LAD at baseline. Among patients in SR, those with a LAD>48mm had the greatest risk of stroke (4.8%/year vs 0.5%/year, p<0.01; Hazard Ratio [HR]: 8.56, 95% C.I. 2.03–36.15). At Cox multivariable regression analysis, LA (HR: 1.104, 95%C.I. 1.039–1.173, p=0.001) and AF (HR: 0.310, 95% C.I. 0.102–0.939, p=0.038) were associated with incident stroke. Conclusions: In HCM patients with CIED long-term monitoring and no prior history of AF, stroke rates were similar in those with de novo AF or stable sinus rhythm. CHA2 DS2 -VASc considerably underestimated risk, whereas severe LA dilatation was a powerful predictor of risk, irrespective of AF. Funding Acknowledgement: Type of funding sources: None.